An EPQ Model for Delay Deteriorating Products With Price, Freshness and Greening Efforts Dependent Demand Under Markdown Strategy - Katariya, Dharmesh K; Shukla, Kunal Tarunkumar (Yugoslav Journal of Operations Research; Vol 34 No 1 (2024), 2023)
Consumers today use green, fresh, perishable products because of their freshness, healthfulness, and sustainability. In this article, we developed the continuous production inventory model for the producer who produces and sells fresh perishable products with the input of green efforts. There are two distinct kinds of product decay to take into account: products whose physical condition gradually deteriorates over time at a constant rate, and products whose freshness quality declines with time. Product demand is influenced by the selling price of the product, its freshness level, and its greening efforts. In order to increase the sales of inventory and enhance the profit from clearing stocks at the end of their life, we have adopted the markdown policy. Due to freshness degradation, a markdown strategy is adopted after a period of product deterioration to boost demand. The objectives of the study are to find out the optimal period for replenishment cycle time, the optimal value of greening efforts, and the optimal markdown percentage such that the producer’s total profit is maximum. A numerical example is used to validate a mathematical formulation that reflects real-world circumstances. A sensitivity analysis of the parameters is done to determine the model's reliability. Some significant managerial results are provided, and the article concludes with a consideration of the future scope of related research.